ANALISIS STRATEGI KEPALA SEKOLAH DALAM PENILAIAN KINERJA GURU PADA KURIKULUM MERDEKA DI SDN CIKARET - Nurhasanah; Dyah Lyesmaya; Iis Nurasiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the principal's strategy in assessing teacher performance in the implementation of the Merdeka Curriculum at SDN Cikaret. The Merdeka Curriculum is the focus of the study because it is a new innovation in the world of education in Indonesia that emphasizes relevant, inclusive, and student-oriented learning. This study uses a qualitative research method. case study approach by collecting data through in-depth interviews, observations, and analysis of related documents. The principal at SDN Cikaret has succeeded in developing a teacher performance assessment strategy that is in accordance with the principles of the Merdeka Curriculum. The development of comprehensive and relevant assessment instruments and the implementation of training programs for teachers are integral parts of this strategy. So that the implementation of this performance assessment was successfully carried out on time and the assessment results were good. Overall, this study shows the importance of the role of the principal in developing effective strategies in assessing teacher performance in the context of the Merdeka Curriculum can make a significant contribution to improving the quality of education at SDN Cikaret and supporting the realization of national education goals.